2020
DOI: 10.1108/apjie-06-2019-0047
|View full text |Cite
|
Sign up to set email alerts
|

Who is more entrepreneurial? A comparative study of vocational and academic students

Abstract: Purpose Research in the context of an individual’s choice of an entrepreneurial career has looked at effect of perceived self-efficacy (PSE), personality characteristics (PC) and subjective norms on entrepreneurial intentions (EIs). In contrast, the purpose of this paper is to compare these constructs across a vocational student (VC) group and an academic group (AC), in a supportive entrepreneurial ecosystem. It also includes PC of the individuals as a variable. Design/methodology/approach The analysis is ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…This study uniquely addresses the contribution of women entrepreneurs in the world economy which is still an unseen but a powerful benefactor of development. Most of the previous studies focused on micro level by focusing the entrepreneurship in general (Bhattacharyya and Kumar, 2020) or specifically for female entrepreneurs (Sidratulmunthah et al, 2018). These studies used the primary data, and their main focus was to address the antecedents of entrepreneurship in the context of educational institutions.…”
Section: Women Entrepreneurs In Economic Developmentmentioning
confidence: 99%
“…This study uniquely addresses the contribution of women entrepreneurs in the world economy which is still an unseen but a powerful benefactor of development. Most of the previous studies focused on micro level by focusing the entrepreneurship in general (Bhattacharyya and Kumar, 2020) or specifically for female entrepreneurs (Sidratulmunthah et al, 2018). These studies used the primary data, and their main focus was to address the antecedents of entrepreneurship in the context of educational institutions.…”
Section: Women Entrepreneurs In Economic Developmentmentioning
confidence: 99%
“…Individuals with high perceived behavioural control are likely to be more motivated to perform a particular behaviour and to be persistent in efforts to engage in the behaviour (Yzer, 2012). It is suggested that conceptually, perceived behavioural control is the same as self-efficacy (Byabashaija et al, 2011;Bhattacharyya and Kumar, 2020). Therefore, these people with high perceived behavioural control believe that they are capable of, or have control over becoming entrepreneurs.…”
Section: Undergraduate Students In Ghanamentioning
confidence: 99%
“…installation and maintenance of electric motors, etc. Bhattacharyya and Kumar (2020) found that vocational curricula provide more practical-oriented training to the students. Despite the rigorous entrepreneurial training process in technical colleges, many of the EIMW students roam the street in search of blue-collar jobs in industries backsliding from the core objectives of entrepreneurial education and training received.…”
Section: Intentions Of Electrical Installationmentioning
confidence: 99%
“…Ohanu et al (2020) stated that EIMW is an area of specialization in Vocational and Technical Education programme of technical colleges in Nigeria, designed to impart knowledge and practical skills in different engineering trade areas such as house wiring (conduit and surface), coil winding and re-winding, electrical gadgets repairs, installation and maintenance of electrical machines, battery charging, installation and maintenance of electric motors, etc. Bhattacharyya and Kumar (2020) found that vocational curricula provide more practical-oriented training to the students. Despite the rigorous entrepreneurial training process in technical colleges, many of the EIMW students roam the street in search of blue-collar jobs in industries backsliding from the core objectives of entrepreneurial education and training received.…”
Section: Introductionmentioning
confidence: 99%